Penerapan Projek Balon Aturan Sekolahku Berbasis PjBL terhadap Hasil Belajar Siswa pada Materi Pancasila - Laila Himmatul Mutammimah; Annisa Rizqi Pratiwi; Susilo Tri Widodo; Hari Kiswanto (ARZUSIN, 2025)
Although Pancasila instruction in elementary schools has been widely examined, studies that specifically address the integration of Project Based Learning (PjBL) with school rules as a contextual project remain limited. This study aimed to evaluate the effectiveness of implementing the “Balon Aturan Sekolahku” project based on Project Based Learning (PjBL) in improving students’ learning outcomes in Pancasila content. A quantitative approach with a one-group pretest–posttest experimental design was employed, involving 25 third-grade students selected through total sampling. Data were collected using learning achievement tests and teacher interviews, and were analyzed using descriptive statistics, paired t-tests, and effect size calculations (Cohen’s d). The results showed a significant increase in students’ learning outcomes, with the mean score rising from 66.04 (pretest) to 78.80 (posttest) and an average N-Gain of 0.352 (medium category). These findings contribute to the development of social constructivist theory and broaden understanding of the application of contextual Project Based Learning (PjBL) in Pendidikan Pancasila instruction. The study concludes that contextual projects such as the Balon Aturan Sekolah initiative play an important role in enhancing students’ knowledge, attitudes, and Pancasila values, and recommends that teachers adopt similar project-based strategies to strengthen student engagement and character formation. The implications of this research include theoretical contributions to the literature on Project Based Learning (PjBL) in primary education and practical recommendations for schools to integrate contextual projects into the Kurikulum Merdeka, while also opening avenues for further research on the longitudinal implementation of Project Based Learning (PjBL) and its effectiveness across diverse school contexts.